Perspectives on improving wound care for Aboriginal health workers in rural and remote communities in Queensland, Australia - Helena J. King; Eliza J. Whiteside; Raelene Ward; Kate Kauter; Martin Byrne; Vicki Horner; Helen Nutter; Jackie Lea (BMC, 2024)
Abstract Background The care of wounds is an ongoing issue for Indigenous people worldwide, yet culturally safe Indigenous wound care training programs for rural and remote Australian Aboriginal Health Workers are largely unavailable. The higher prevalence of chronic disease, lower socioeconomic status and poorer access to services experienced by Aboriginal and Torres Strait Islanders compared to non-Indigenous people, leads to a greater incidence of chronic wounds in Aboriginal and Torres Strait Islander people. Identifying the barriers and enablers for delivering wound care will establish areas of need for facilitating the development of a specific wound care program for Aboriginal Health Workers and Aboriginal Health Practitioners. This paper reports the first phase of a larger project directly aligned to the Indigenous Australians' Health Program's objective of supporting the delivery and access to high quality, culturally appropriate health care and services to Aboriginal and Torres Strait Islander Australians. This study aimed to examine experiences of Aboriginal Health Workers, Aboriginal Health Practitioners, and nurses for managing chronic wounds within rural and remote Aboriginal Medical Services in Queensland, Australia. Methods Yarning facilitated by two Aboriginal researchers among Aboriginal Health Workers, Aboriginal Health Practitioners, and nurses currently employed within four Aboriginal Medical Services located in rural and remote areas of Queensland, Australia. Results Two themes were developed through rigorous data analysis of yarning information and responses: participants' experiences of managing wounds and barriers and enablers to effective wound care. Conclusions This study contributes an insight into the experiences of Aboriginal Health Workers on the current barriers and enablers to timely treatment of chronic wounds. Results from this study indicate a significant barrier to obtaining timely and effective wound care in regional and remote settings is access to an appropriately skilled, culturally competent, and resourced health work force. A lack of education and professional development for Aboriginal Health Workers can compromise their ability to maximise patient outcomes and delay wound healing. Findings have informed the development of an evidence based, culturally competent open access chronic wound care education program for Aboriginal Health Workers.